Cell Therapies in Tendon, Ligament, and Musculoskeletal System Repair. Issue 2 (June 2018) - de Albornoz, Pilar M.; Aicale, Rocco; Forriol, Francisco; Maffulli, Nicola
Abstract : In the last few decades, several techniques have been used to optimize tendon, ligament, and musculoskeletal healing. The evidence in favor of these techniques is still not proven, and level I studies are lacking. We performed an analysis of the therapeutic strategies and tissue engineering projects recently published in this field. Here, we try to give an insight into the current status of cell therapies and the latest techniques of bioengineering applied to the field of orthopedic surgery. The future areas for research in the management of musculoskeletal injuries are outlined. There are emerging technologies developing into substantial clinical treatment options that need to be critically evaluated. Mechanical stimulation of the constructs reproduces a more propitious environment for effective healing.